COVID-19’s varied impacts on fresh fruit and vegetable supply chains in Senegal - Fabry, Anna; Van Hoyweghen, Kaat; Feyaerts, Hendrik; Wade, Idrissa; Maertens, Miet (International Food Policy Research Institute, 2022)
In response to the COVID-19 pandemic, Senegal declared a state of emergency on March 23, 2020, followed by a range of policy measures to prevent the spread of the coronavirus: Transport was significantly restricted, wet markets were closed, and shops were required to limit their hours. These moves disrupted food supply chains, in particular, those for highly perishable products such as fresh fruits and vegetables (FFV).